Some mathematical problems in genetics - Radavičius, Marijus; Rekašius, Tomas; Židanavičiūtė, Jurgita (Lietuvos matematikos rinkinys, 2007)
After an introduction to genetic basics three problems are briefly discussed: microarray data analysis, a definition of noninformative DNA sequence, and genetic sequence alignment. More atention is paid toDNA sequence visualization and regularization of a genome signature.
Keywords: alignment; discrete Sobolev norm; DNA sequence; genetic noise; Markov chain; microarray; multidimensional scaling; noninformative sequence; regularization; stationary distribution